Repercussão na saúde mental de crianças e adolescentes na vigência da pandemia da covid-19 em região de fronteira - Canonico, Simone Daniela Bif (2024)
The Covid-19 pandemic raised concerns about behavior and lifestyle changes, which impacted the children’s and adolescents’ mental health and well-being, especially those who live in disadvantaged socioeconomic environments. The present study aimed to analyze the repercussions of the Covid-19 pandemic on the mental health of children and adolescents treated at the Center for Psychosocial Care for Children and Adolescents in a city located in a Border Region. This is a cross-sectional study, carried out by collecting data from the medical records of children and adolescents aged between zero and eighteen years old, treated from January 2018 to December 2022. Collection was carried out from April to May 2023, at the Child and Youth Psychosocial Care Center in Foz do Iguaçu, using a questionnaire prepared on Google Forms, to collect sociodemographic and clinical variables recorded in the medical records. The data were exported to Excel spreadsheets and the Jamovi software and Pearson's Chi-square test were used to carry out statistical analyses. During the research period, 1,457 patients were treated, of which 71.9% (n=1047) were adolescents, with a predominance of females, 53.3% (n=777), with 48% (n=700) living with an only parent. The most frequent diagnoses among adolescents and children were depressive episodes and anxiety disorders. The main complaints at the time of admission were suicidal thoughts 29% (n=434) and depressive symptoms 25.8% (n=376). There was a significant increase during the Covid-19 pandemic in symptoms among children of suicidal thoughts 84.4% (n=34), anxiety 74.6% (n=53), self-harm 92.1% (n=35) and aggression 55.6% (n=79), adolescents had greater mental health problems related to suicidal thoughts 65.3% (n=254), suicide attempts 67.3% (n=111), anxiety 81.4% (n=232) and self-harm 69.5% (n=196). The medicinal approach was the most used during the pandemic, there were decreases in approaches aimed at therapeutic practices, and in cases of psychiatric hospitalization during the pandemic. This study made it possible to understand the psychosocial demands of CAPSi users in Foz do Iguaçu and concluded that the Covid-19 pandemic had a negative impact on children’s and adolescents’ mental health living in an international border region, given the worsening of symptoms. It is expected that the results obtained in this study enable to deepen knowledge on the topic and contribute to the promotion and care regarding the children’s and adolescents’ mental health, as well as offering content to think about the construction of public policies that guide mental health in periods of major crises and epidemics.